Reengineering the administrative processes and their relationship with the quality of work in the Institute of Science and Techniques of Physical and Sports Activities in M’sila . - rabah.berbakh (sports creativity, 2025)
Our objective through this study, entitled Reorganizing Administrative Processes and Its Relation to the Quality of the Work of the M'sila Institute of Science and Technology in Physical and Sports Activities, consists of: To identify the nature of the relationship between the reengineering of administrative processes and the quality of work at the M'sila Institute of Science and Technology of Physical and Sports Activities and to identify the nature of the relationship between the design of the organizational structure and the quality of work and the nature of the relationship between the capabilities of information technology and the quality of work. The class of the study was a community of professors from the Institute of Science and Technology of Physical and Sports Activities of M'sila A random sample of 43 teachers was selected out of 121. • There is a statistically significant relationship between the design of the organizational structure and the quality of the work done at the M'sila Institute of Science and Technology for Physical and Sports Activities. • There is a statistically significant relationship between the capabilities of information technology and the quality of work at the M'sila Institute of Science and Technology for Physical and Sports Activities.